Industrial Scale Reactor Design for Al2O3 Production from Bauxite and Sodium Hydroxide Solution - Nissa, afviva; Nandiyanto, Asep Bayu Dani; Ragaditha, Risti (Journal of Industrial and Engineering System, 2023)
The aim of this study is to design a reactor that can optimize the production of Al2O3 from the reaction between bauxite and sodium hydroxide solution on an industrial scale. The type of reactor used for the production of Al2O3 nanoparticles is a Continuous Flow Stirred – Tank Reactor (CSTR). The method used in this study is to perform computational analysis and calculation of the dimensions of the reactor and stirrer as well as the mass balance, using basic calculation with Microsoft Excel application. To produce Al2O3 nanoparticles on an industrial scale, three reactor units and three stirrers are required. Based on the calculation results, it is found that the first and second reactors have volume 2,9689 m3 with height 5,0424 ft and require a stirrer with six blades with an angle of 45owhich has power 50 Hp. The third reactor has volume 4,3387 m3 with height 9,0847 ft and requires one stirrer with six blades with an angle of 45o which has a power 75 Hp. The computational calculation results in this study can be used as an overview in designing a reactor to produce Al2O3nanoparticles from bauxite and sodium hydroxide solution on an industrial scale